The impact of age and frailty on hospitalization and survival in older liver transplant recipients: a longitudinal cohort study - Valenti, Matteo; Ceolin, Chiara; Rossato, Marco; Curreri, Chiara; Devita, Maria; Tonon, Marta; Campodall’Orto, Carlotta; Vanin, Jessica; Gambato, Martina; Cillo, Umberto; Burra, Patrizia; Angeli, Paolo; et al. (Frontiers in Aging, 2025)
PurposeFrailty is a well-established risk factor for adverse outcomes, particularly in liver transplant candidates. This study investigates the impact of age and frailty on key clinical outcomes—hospitalizations, waitlist survival, and post-transplant mortality—in cirrhotic patients evaluated for liver transplantation.MethodsThis study included older adults with chronic liver disease under consideration for transplantation. Data collected encompassed medical history, Model for End-Stage Liver Disease (MELD) and Child-Turcotte-Pugh (CTP) scores, Mini-Mental State Examination (MMSE), Mini Nutritional Assessment (MNA), and frailty status, assessed using both the Liver Frailty Index (LFI) and the Survey of Health, Ageing, and Retirement in Europe Frailty Index (SHARE-FI). Clinical outcomes, including mortality and hospitalizations, were tracked over a 24-month period.ResultsAmong 100 patients (67% male), those under 70 exhibited higher MNA, MMSE, and SHARE-FI scores. Based on frailty classification, 25 patients were frail, 28 pre-frail, and 47 robust. Younger patients experienced more hospitalizations during follow-up (p = 0.03) and had a higher probability of hospitalization within 24 months (p = 0.002). Although transplant-free survival did not differ significantly across groups, frail patients had a significantly higher mortality rate (p = 0.04). Overall, 24 patients underwent transplantation, while 26 died, including six post-transplant deaths. MELD and CTP scores were strong predictors of mortality, while among frailty measures, only SHARE-FI demonstrated significant predictive value. In multivariate Cox models, MELD [HR = 1.17, p = 0.001; HR = 1.11, p = 0.002], CTP [HR = 1.43, p = 0.003; HR = 1.41, p = 0.006], and LFI (HR = 1.69, p = 0.04) were significantly associated with mortality.ConclusionFrailty, rather than age, emerges as a key predictor of mortality in liver transplant candidates. Further research is needed to validate these findings and enhance frailty assessment, ultimately improving candidate selection for transplantation.